Utilization of Spatial Data on Agricultural Activities Case Study of Tebas District - Ludovicus Manditya Hari Christanto; Irwansyah Irwansyah (CV. Rayyan Dwi Bharata, 2023)
The dominant potential of agricultural activities is not in line with the dissemination of adequate information on agricultural activities, thus causing agricultural activities in Tebas District to be unknown to the wider community. Information about agricultural activities will be more easily accessed by the community in Tebas District with the existence of a web-based geographic information system where people can get non-spatial information and also spatial information from agricultural activities in Tebas District. The purpose of the study is to determine the use of GIS web applications in monitoring agricultural activities. The research location focused on the Tebas Komplek agricultural area which is designated as a sustainable food agriculture area in Sambas regency which includes Tebas Sungai Village, Pangkalan Kongsi Village, Dungun Perapakan Village, Serumpun Buluh Village and Mekar Sekuntum Village. The research method used in this study used remote sensing and waterfall methods. The remote sensing method is used to build spatial data by using remote sensing imagery, while the waterfall method is used to build a home GIS web for spatial data to be placed. The technique of collecting data on attributes of agricultural activities is carried out by filling out questionnaires, while spatial data collection is carried out by interpreting satellite images and testing the accuracy and tracking of land in the field. The results of the study stated that: 1) A Web Gis application design has been composed which contains the home page, poktan data page, poktan detail page, whole rice field data page, member detail page, login page, poktan data input page, and rice field data input page; 2) The agricultural land system in Serumpun Buluh Village has its own uniqueness compared to Mekar Sekuntum village, Tebas Sungai, Dungun Perapaakan and Pangkalan Kongsi in Tebas Agricultural Area Complex, which uses an overlay system. Serumpun Buluh Village uses a domicile system, which is based on the domicile of farmers and some are based on the location of land owned by farmers; 3) There are differences in the variation in the area of poktan spatial data in each gappoktan located in the Tebas Complex Agricultural Area. The conclusion of the use of the gis web application will make it easier for extension workers and gapoctans to monitor agricultural activities in the Tebas Komplek agricultural area.